2005
DOI: 10.1007/s10551-004-5367-z
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility and Long-term Compensation: Evidence from Canada

Abstract: This paper examines the association between long-term compensation and corporate social responsibility (CSR) for 90 publicly traded Canadian firms. Social responsibility is considered to include concerns for social factors and the environment (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
137
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(143 citation statements)
references
References 39 publications
1
137
4
1
Order By: Relevance
“…More specifically, prior literature has reported a significant relationship between CSR and incentive-based compensation (Falck and Heblich 2007;Mahoney and Thorne 2005). Also, Jones et al (2007), in their case study involving Australian companies, found that the extent to which a firm is involved in CSR was directly correlated to its adopting a performance-based wage system.…”
Section: Hypothesesmentioning
confidence: 95%
“…More specifically, prior literature has reported a significant relationship between CSR and incentive-based compensation (Falck and Heblich 2007;Mahoney and Thorne 2005). Also, Jones et al (2007), in their case study involving Australian companies, found that the extent to which a firm is involved in CSR was directly correlated to its adopting a performance-based wage system.…”
Section: Hypothesesmentioning
confidence: 95%
“…Previous research, which has looked at the relationship between executive compensation and CSR (Frye et al, 2006;Mahoney and Thorne, 2005;McGuire et al 2003), has mainly focused on CEO's flow compensation. The arguments shared by this stream of research rely on the fact that CSR may lead the company to forgo short-term profits to invest in projects that have no immediate payoff.…”
Section: Background and Motivationmentioning
confidence: 99%
“…In recent years there has been an increasing interest in CSR, which has led to wide press coverage and a growing number of academic research papers on the topic (Mahoney and Thorne 2005). As pointed out by Porter and Kramer (2006, p. 78), governments, activists and the media have become adept at holding companies to account for the social consequences of their activities and many organizations have started ranking companies on their CSR performance, attracting considerable publicity.…”
Section: Introductionmentioning
confidence: 99%
“…Only salary and long-term incentives are found to be statistically significant in the social weaknesses model. With a similar research design, Mahoney and Thorne (2005) provide evidence that only some elements of compensation matter to certain measures of sustainability.…”
Section: Linking Sustainability To Compensation: Emerging Practices Amentioning
confidence: 99%